(untitled) (Journal of Misan Researches, 2024)
Evaluation of the English language book for the fourth stage of primary school (English for Iraq) from the point of view of teachers and supervisors The aim of the current research is to evaluate the English language book for the fourth grade of primary school from the point of view of teachers and supervisors, and to identify suggestions from the research sample for developing this book. . for developing and improving the English language book for the fourth stage of primary school and teaching the English language in Iraq in general? The researcher followed the descriptive approach, and to achieve this goal, a random sample of English language teachers and supervisors, representative of the original community, was chosen. It amounted to (100) male and female teachers and (10) supervisors from the General Directorate of Missan Education. The researcher adopted the questionnaire as a tool for his research, and it was distributed electronically to the sample. The questionnaire consisted of (64). Items divided into four domains: (objectives, content, educational activities, evaluation). To treat the data statistically, the researcher used (percentages, chi-square, Pearson correlation coefficient, Cronbach’s alpha equation, weighted means, standard deviations, and percentage weights). The result of the research was that the comprehensive quality standards in the English language book for the fourth grade of primary school were achieved to a weak degree